Healthy Eating for Elders: Creating a No-Cook Meal - Jennifer Hillan (EDIS)
What’s for supper when you don’t feel like cooking? Think of foods to use for a well-balanced, no-cook meal. Then put the foods where they belong in the pyramid illustrated on this leaflet.